PEMANFAATAN BAHAN LOKAL DALAM DIVERSIFIKASI PRODUK PANGAN SECARA MANDIRI OLEH IBU-IBU KELOMPOK PENGAJIAN BTN MANUSELA KOTA AMBON - Cecilia Anna Seumahu; Deli Wakano; Efraim Samson; Dece Elisabeth Sahertian (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The nutritional content of snail meat is in the form of protein (> 50%) and only a small portion is in the form of fat (5%). But it is used only as a food source of protein with limited processing. The purpose of this activity is to introduce the diversification of snail product food and practice it independently to the member of Kelompok Pengajian. The method used in this service includes several stages, the initial approach with group leaders and scheduling activities, making nuggets and meatballs on a laboratory scale, conducting meetings with member of the group through online link and practice it on several mothers at home. In addition, information was provided in the form of nuggets and meatball leaflets and house of the members. Results obtained from this activies are an increase in knowledge about the use of sea snails not only in the form of snail curry, but the diversification of sea snails product such as nuggets and snail meatballs. Leaflets and videos were produced to simplify the working procedure for making nuggets and meatballs in each house while staying at home.